"To study the impact of Technology on the Academic Achievement of Tribal Children of Higher Secondary School of Chhattisgarh" - Narad, Navneet Kaur (International Journal of Computer Sciences and Engineering, 2025)
Rural Education System needs implementation of e-learning technologies. In 2004 Edusat was launched by ISRO to support education by presenting the education videos. Indian government is making efforts to connect villages to the internet through platforms like e-Panchayat. There are schemes for rolling out inexpensive tablets called „Aakash‟. It has become increasingly clear during the past decade that the general level of academic achievement of higher secondary tribal students is increasing. “The destiny of India is now being shaped in their classrooms”.